-4(2t-2)+3t=4t-6

Simple and best practice solution for -4(2t-2)+3t=4t-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2t-2)+3t=4t-6 equation:


Simplifying
-4(2t + -2) + 3t = 4t + -6

Reorder the terms:
-4(-2 + 2t) + 3t = 4t + -6
(-2 * -4 + 2t * -4) + 3t = 4t + -6
(8 + -8t) + 3t = 4t + -6

Combine like terms: -8t + 3t = -5t
8 + -5t = 4t + -6

Reorder the terms:
8 + -5t = -6 + 4t

Solving
8 + -5t = -6 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
8 + -5t + -4t = -6 + 4t + -4t

Combine like terms: -5t + -4t = -9t
8 + -9t = -6 + 4t + -4t

Combine like terms: 4t + -4t = 0
8 + -9t = -6 + 0
8 + -9t = -6

Add '-8' to each side of the equation.
8 + -8 + -9t = -6 + -8

Combine like terms: 8 + -8 = 0
0 + -9t = -6 + -8
-9t = -6 + -8

Combine like terms: -6 + -8 = -14
-9t = -14

Divide each side by '-9'.
t = 1.555555556

Simplifying
t = 1.555555556

See similar equations:

| xy+5x-10+2y= | | -2(4x-1)+9=-8x+11 | | .3x+5.35=9 | | 3x^2(2-x+4x^2)= | | 3x+3=3(x+8) | | -5w=10/7 | | -7w/9=-35 | | 5/6x+7/8-3/7x | | 6+2/3(12) | | -3/8w=-12 | | 4(x-1)+7=2x+2(1-x) | | -9y-9=8y+25 | | .3x+5.35=7 | | -7/8=w-2 | | .3x+5.35=6.88 | | -1/4+v=2/5 | | 10*t=5.8392 | | 3+12f=30 | | (1/10)x-11=(3/5)x | | 0.75t-0.85=0.66t | | 4+6f=24 | | 0.75t-0.85=0.6t | | 2+12f=24 | | 5x-3=4-3x | | 0.3(5)+5.35=y | | 41.6=r+9.2 | | 0.3(3)+5.35=y | | 2+9f=18 | | 2+6f=18 | | 3+6f=18 | | 3+5f=15 | | 33*17= |

Equations solver categories